Two new species of Philometra (Nematoda: Philometridae) from needlefishes (Belonidae) in Iraq, with a key to Philometra spp. parasitic in the host's subcutaneous tissue, fins and musculature - Moravec, Frantisek; Ali, Atheer Hussain (Folia parasitologica, 2005)
Two new nematode species, Philometra strongylurae sp. n. and Philometra tylosuri sp. n., are described from female specimens collected from needlefishes (Belonidae, Beloniformes) off the Fao coast, Basrah, Persian Gulf, in Iraq. Philometra strongylurae (gravid females with larvae) was recorded from the subcutaneous tissue, muscles of beak and gills of Strongylura leiura (type host) and S. strongylura, whereas P. tylosuri (nongravid females) from the musculature and the subcutaneous tissue of Tylosurus crocodilus. The former is characterized mainly by the presence of eight markedly large cephalic papillae, conspicuously large anterior oesophageal bulb and by the length of body (15-20 mm); the latter by eight minute cephalic papillae, poorly developed oesophageal bulb and by the body length (46-72 mm). A key to Philometra spp. with gravid females parasitic in the subcutaneous tissue, fins or musculature of fishes is provided.
Keywords: druhová specificita; Animals; Body Weights and Measures; mikroskopie elektronová rastrovací; Female; zvířata; tělesné váhy a míry; Dracunculoidea; Indický oceán; Species Specificity; Microscopy, Electron, Scanning; Beloniformes; ženské pohlaví; Indian Ocean